Isotopic composition of Pb in peat and porewaters from three contrasting ombrotrophic bogs in Finland: evidence of chemical diagenesis in response to acidification - Shotyk, William; Rausch, Nicole; Krachler, Michael (Environmental science & technology, 2016)
The isotopic composition of Pb was determined in Finnish peat bogs and their porewaters from Harjavalta (HAR, near a Cu-Ni smelter), Outokumpu (OUT, near a Cu-Ni mine), and Hietajärvi (HIJ, a background site). At HIJ and OUT, the porewaters yielded similar concentrations (0.1-0.7 μg/L) and isotopic composition (206Pb/207Pb = 1.154-1.164). In contrast, the peat profile from HAR yielded greater concentrations of Pb in the porewaters (average 2.4 μg/L), and the Pb is less radiogenic (206Pb/207Pb = 1.121-1.149). Acidification of the bog surface waters to pH 3.5 by SO2 emitted from smelting (compared to pH 4.0 at the control site) apparently promotes the dissolution of Pb-bearing aerosols, as well as desorption of metals from the surfaces of these particles and from the peat matrix. Despite this, the chronology of anthropogenic, atmospheric deposition for the past millenium recorded by the isotopic composition of Pb in all three peat bogs is remarkably similar. While the immobility of Pb in the peat cores may appear inconsistent with the elevated porewater Pb concentrations, Pb concentrations in the aqueous phase never amount to more than 0.01% of the total Pb at any given depth so that the potential for migration remains small. The low rates of vertical water movement in bogs generally combined with the size of the metal-containing particles in solution may be additional factors limiting Pb mobilization.
Gesehen am 06.05.2020